Development Controls in Toronto in the Nineteenth Century - Fischler, Raphaël (Urban History Review / Revue d'histoire urbaine, 2007)
Histories of contemporary development control tend to situate its beginning in the first or second decade of the twentieth century, when modern zoning bylaws were adopted. Yet, as some researchers have pointed out, building and land-use regulations took shape in the nineteenth century and even earlier. This paper focuses on controls set by the City of Toronto between 1834, when it was incorporated, and 1904, when it adopted bylaw no. 4408, which is seen by many as the first step taken by the city toward modern zoning. In technical terms, it appears that a coherent, though minimal, apparatus of land-use regulation was already in place by the 1860s. Over the course of the nineteenth century, building codes and nuisance laws display the growing intervention of public authorities in the development of the industrial city. Municipal control over material production and over human activity diversifies and finds expression in increasingly complex ordinances. In political terms, the bylaws reveal a growing concern with socio-spatial differentiation and with the protection of property values rather than with health and safety. The incremental development of land-use regulation suggests that, even though North American cities borrowed from each other and from their European counterparts, they constructed zoning locally, in accordance to local needs, resources, and constraints (economic, political, and legal) and in a piecemeal fashion, one bylaw, one amendment at a time.